Pengaruh Non Performing Financing, Return On Assets, dan BOPO pada Kondisi Financial Distress pada BPRS di Jawa Barat 2020-2023 - Zahra Hasna Muzaki; Riyandi Nur Sumawidjaja (Komunitas Dosen Indonesia, 2024)
This study was conducted to determine the risk of financial distress of Islamic Rural Credit Banks in West Java for the period 2020-2023 using the Springate S-score calculation model. The financial ratios used in this study are NPF, ROA and BOPO. The data in this study were 32 data, namely 4 years of time series data on 8 Islamic Rural Credit Banks obtained through the official Islamic banking statistics website of the Financial Services Authority (https://www.ojk.go.id). The data analysis used in this study was multiple regression. Based on the results of the study (1) Non Performing Financing (NPF) partially has no negative and insignificant effect on Financial Distress (increase in Score value) with a magnitude of influence of 10.4%. (2) Return On Asset (ROA) partially has a positive and significant effect on Financial Distress (increase in S-score value). With a magnitude of influence of 40.5%. (3) BOP) has no positive and significant effect on Financial Distress (increase in S-score value). With a magnitude of influence of 19.4%. (4) NPF, ROA and BOPO simultaneously affect the financial distress condition at Islamic Rural Credit Banks in West Java in 2020-2023 with a determination coefficient value of 41.5. While the remaining 58.5% is influenced by other variables not examined in the study.